Dinasti Dinasti yang Membebaskan Diri Dari Baghdad - Basri, Muhammad; Natasya, Astrid; Wiranti, Winy (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research presents an in-depth analysis of the dynasties that liberated themselves from Baghdad's rule in certain historical periods, with a focus on the Umayyad Dynasty, Aghlabiyah Dynasty, and Fathimiyyah Dynasty. A qualitative approach is used to explore the factors that drive this political separation through historical analysis, literature studies, and interviews with historians. Research findings identified three key factors. First, political pressure from the Baghdad central government emerged as the main trigger for secession. These dynasties responded to political pressure in the form of fiscal and military policies that were considered burdensome, prompting them to seek autonomy in managing internal affairs and economic resources. Second, cultural differences play a crucial role in the dynamics of secession. Dynasties sought independence to preserve and promote their own cultural heritage, language, and religious identity, which was threatened by the cultural homogenization of the center of power. Third, aspirations for autonomy, both in terms of local policy and cultural identity, were the main driving force behind the dynasties' decisions to secede. They desired greater control over their own internal affairs, economic resources, and identity, driving efforts to achieve political independence. The results of this research provide deep insight into the complexity of political and cultural factors that shape secession dynamics. This understanding not only contributes to a structural understanding of politics in the past, but also details the spirit of maintaining diversity and local identity amidst political pressure. Findings. This can provide a basis for further research on political and cultural developments in regions experiencing separation from the center of power.